2018
DOI: 10.31501/rbpe.v8i1.8319
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da prática de musculação nos estados de humor de jovens aprendizes

Abstract: Objetivo: verificar os efeitos da atividade física nos estados de humor no ambiente de trabalho. Método: Foram avaliados 56 Jovens Aprendizes de uma empresa sendo 42 do sexo masculino e 14 do sexo feminino. O instrumento utilizado para coleta dos dados referentes à avaliação do estado de humor foi o questionário BRAMS, que contém 24 itens organizados em seis dimensões: tensão, depressão, raiva, vigor, fadiga e confusão. Cada item é avaliado em uma escala de cinco pontos (0 = nada a 4 = extremamente), sendo o s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is interesting to observe that variables such as depression, anger, and mental confusion were not statistically different, revealing that these variables seem to be less sensitive to acute exercise. 42 In another study, de Melo et al 43 demonstrated improvement in mental health after just one session of strength training (ST), resulting in a profile of positive mood state, with low values of negative scores and a high value of the positive score (vigor). A possible explanation for these effects is that the psychological benefits of exercise occur both as a result of physiological factors, such as increased physical fitness, and increased levels of neurotransmitters in the brain, such as endorphins, serotonin, and α brain waves that act to improve the quality of sleep, 44 and of psychological and social factors, such as increased self-esteem, selfefficacy, feelings of pleasure, and contact with people.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to observe that variables such as depression, anger, and mental confusion were not statistically different, revealing that these variables seem to be less sensitive to acute exercise. 42 In another study, de Melo et al 43 demonstrated improvement in mental health after just one session of strength training (ST), resulting in a profile of positive mood state, with low values of negative scores and a high value of the positive score (vigor). A possible explanation for these effects is that the psychological benefits of exercise occur both as a result of physiological factors, such as increased physical fitness, and increased levels of neurotransmitters in the brain, such as endorphins, serotonin, and α brain waves that act to improve the quality of sleep, 44 and of psychological and social factors, such as increased self-esteem, selfefficacy, feelings of pleasure, and contact with people.…”
Section: Discussionmentioning
confidence: 99%